2001
DOI: 10.1021/la001038s
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Silver Colloidal Particles Obtained by Citrate Reduction To Increase the Raman Enhancement Factor

Abstract: A method is reported for obtaining silver colloids with a large particle size. It is based on the growth of seed colloidal particles obtained by chemical reduction of silver nitrate with citrate. These colloids were characterized by means of UV-visible spectroscopy and transmission electron microscopy. The nucleation mechanism is discussed on the basis of the morphology and size of the resulting particles. Moreover, the surface-enhanced Raman scattering activity of the resulting colloids was evaluated in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(113 citation statements)
references
References 12 publications
5
106
1
1
Order By: Relevance
“…More homogeneous and slightly smaller metal particles can be achieved with deposition of metal colloids on the surface. This results in particles with a 20-30nm diameter [62][63][64][65]. We observed that under carefully controlled experimental conditions, it is possible to achieve particle aggregates of metal colloids on the substrate surface.…”
Section: Silver Colloid Coated Surfaces (Sccs)mentioning
confidence: 93%
“…More homogeneous and slightly smaller metal particles can be achieved with deposition of metal colloids on the surface. This results in particles with a 20-30nm diameter [62][63][64][65]. We observed that under carefully controlled experimental conditions, it is possible to achieve particle aggregates of metal colloids on the substrate surface.…”
Section: Silver Colloid Coated Surfaces (Sccs)mentioning
confidence: 93%
“…Organics like sodium citrate, ascorbic acid and amino acids capable of being oxidized also used as alternate methods, (Rivas et al, 2001;Zhu Shiguo et al, 2002). All the silver nanoparticles preparations showed partical size of 20-25nm.…”
Section: Gene/drug Deliverymentioning
confidence: 99%
“…From the originally used metal electrode 15,16 to metal colloid systems, [17][18][19] the researches about SERS-active substrate have been explored extensively to develop much higher enhancement ability and stability. Silver and gold colloids are most frequently employed metallic systems in SERS.…”
Section: Introductionmentioning
confidence: 99%